Influence of superionic nanoparticles Cu₆PS₅I on dielectric properties of nematic liquid crystal 6СНВТ - Studenyak, I.P.; Demko, P.Yu.; Bendak, A.V.; Kovalchuk, O.V.; Kovalchuk, T.M.; Lisý, V.; Kopčanský, P.; Timko, M.; Tomašovičová, N.; Zavisova, V.; Gdovinova, V.; Miskuf, J.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Within the frequency range 10…10⁶ Hz, the influence of Cu₆PS₅І nanoparticles on the dielectric properties of planar oriented liquid crystal 6СНВТ has been studied. It has been shown that nanoparticles lead to an increase in conductivity, but the conductivity dependence on concentration is non-monotonic function. It has been suggested that the reason of non-monotonic dependence of conductivity of 6СНВТ on the concentration of nanoparticles is significant influence of ion adsorption on the nanoparticle surface and increase in the viscosity of liquid crystal when introducing nanoparticles.